Clinical Utility of Procalcitonin for Stratifying Severity in Sepsis Secondary to Pneumonia - Saputra , Wachyoe Hadi; Prima, Agus; Wirdah, Wirdah (Journal of Society Medicine, 2026)
Introduction: Procalcitonin (PCT) is a biomarker that reflects the systemic inflammatory response to bacterial infections and has been widely studied in the context of sepsis. In patients with pneumonia, early identification of the severity of sepsis is essential for appropriate clinical management and prognostic evaluation. This study aimed to assess the clinical utility of serum procalcitonin levels in stratifying sepsis severity in patients with pneumonia. Methods: This analytical cross-sectional study was conducted between February 2013 and March 2014 in the Emergency Department and Internal Medicine Wards of Dr. Zainoel Abidin General Hospital in Banda Aceh, Indonesia. Thirty patients diagnosed with pneumonia were enrolled in this study using quota sampling method. Serum procalcitonin levels were measured and categorized according to the severity of sepsis. Statistical analysis was performed using one-way analysis of variance (ANOVA), followed by the least significant difference (LSD) post-hoc test using the SPSS software. Statistical significance was set at P < 0.05. Results: Serum procalcitonin levels progressively increased with increasing severity of sepsis. The lowest PCT level was observed in patients with pneumonia without sepsis (0.091 ng/mL), followed by those with sepsis (0.686 ng/mL), severe sepsis (3.593 ng/mL), and septic shock (21.703 ng/mL). Significant differences in PCT levels were found across the severity groups (P < 0.05), indicating a strong relationship between elevated procalcitonin levels and worsening clinical severity. Conclusion: Serum procalcitonin levels correlate with the severity of sepsis in patients with pneumonia and may serve as a useful biomarker for sepsis severity stratification and clinical risk assessment.